SEX AND SALT-RESPONSIVE CONJUGATION OF BILE ACIDS BY THE HOLOBIONT REGULATES HYPERTENSION. (April 2021) - Chakraborty, Saroj Chakrabort; Lulla, Anju; Cheng, Xi; Mccarthy, Cameron G; Yeo, Ji-Youn; Alimadadi, Ahmad; Mandal, Juthika; Saha, Piu; Yeoh, Beng San; Louis, Evangelina F; Mell, Blair; Jia, Wei; et al.
Abstract : Objective: Men and women are differently prone to cardiovascular diseases. Salt-sensitive women are more likely to develop aggravated hypertension in response to an overloaded salt diet than men. Men and women also differ in gut microbiota, which regulates both bile acid composition and hypertension; however, whether sex may differentially influence the gut microbial production of bile acids, with attendant effects on hypertension, is not known. We hypothesized that reshaping of gut microbiota by dietary salt is sex-dependent and adversely affects bile acids to promote hypertension. Design and method: To test this hypothesis, groups of male and female salt-sensitive hypertensive (Dahl S) and salt-resistant normotensive (Dahl R) rats (n = 6/gp) on low (0.3% NaCl) or high (2% NaCl) diets were profiled for fecal microbiota by 16S sequencing and serum bile acids by targeted GC-TOF-MS metabolomics. Results: Hierarchical clustering analysis of bile acids with microbiotal profiles revealed that glycine- and taurine-conjugated bile acids were prominently negatively correlated with blood pressure (BP) in female rats, while only taurine-conjugated bile acids were negatively correlated with BP in male rats. These observations were corroborated by microbiotal and bile acid metabolomic profiling of human hypertensive samples from a population-based cohort (CARDIA). Next, to test whether hypertension can be prevented by supplementing substrates for bile acid conjugation, high salt fed S rats were administered with either taurine (3% v/v in drinking water) or glycine (1% v/v in drinking water) in drinking water, monitored for BP by telemetry, and profiled for bile acid metabolites. Both taurine and glycine feeding prevented hypertension in females (Systolic BP: taurine:176 ± 7*, glycine: 182 ± 4*, control: 197 ± 4 mmHg, n = 6–9/gp, *p < 0.05) likely by rescuing levels of levels of respective conjugated bile acids, whereas only taurine, but not glycine, prevented hypertension in males (Systolic BP: taurine: 166 ± 2*, glycine:184 ± 5, control: 184 ± 8 mmHg, n = 5–6/gp, *p < 0.05). Conclusions: Our results connect sex-specific differences in salt-sensitive hypertension to the gut-liver axis and suggests that nutritional restoration of host taurine- or glycine-conjugated bile acids for women and host taurine-conjugated bile acids for men as potential therapeutics for salt-sensitive hypertension.